Magnetic anomalies and model of the magnetization in the Earth's crust of circumpolar and polar the sectors of Ural region - N. V. Fedorova; A. L. Rublev; L. A. Muraviev; V. V. Kolmogorova (Геофизический журнал, 2017)
The study of the structural features of the anomalous magnetic field for the territory of the circumpolar and polar sector of the Urals region was carried out. The anomalies of the Earth's crust layers were identified and the maps of such anomalies were created. Map of local anomalies was used for mapping basic-ultrabasic massifs in the upper parts of the foundation within the sedimentary basins. An interpretation of regional magnetic anomalies was carried out, a model structure of the Earth's crust and their parameters are based on the results of the studies along the DSS profiles. Comparison of the deep structure of the cuts produced by independent geophysical methods based on seismic and magnetic data has enabled us to share the consolidated crust into two layers with different magnetic properties. Top layer of the Earth's crust does not make a significant contribution into regional magnetic field and is characterized by a low magnetization (less than 0,3 A/m). Within this layer magnetized local sources were identified. The lower layer has greater crustal magnetization. As a result of the two-dimensional modeling of the value of the magnetization of the basalt layer of the crust is 3—4 A/m, The average depth to the top surface of the layer is 18—20 km. The resulting parameters were used for three-dimensional modeling, Model with uniform magnetization directed along the modern geomagnetic field has been considered. For the entire region it was built the upper surface of the magnetized layer, which allowed to clarify mafic layer in the space between the DDS profiles. It was found that at the Northern, Circumpolar and Polar Urals basalt layer plunged to a considerable depth of 26—30 km.